Green leadership and climate change awareness effects on police performance: A mediation analysis - Juniar Sitinjak; Sri Indarti; Lailan Tawila Berampu; Samsir Samsir (Journal of Applied Business Administration, 2026)
This study aims to analyze the effects of green leadership and climate change awareness on personnel performance, with pro-environmental behavior as a mediating variable, at the Riau Regional Police. The study adopts a quantitative approach using a survey method. The research population consists of 11,588 personnel, with a sample of 100 respondents selected through proportionate stratified random sampling. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares–based Structural Equation Modeling (SEM-PLS). The results indicate that climate change awareness and green leadership have positive and significant effects on personnel performance. In addition, both variables also significantly influence pro-environmental behavior, which in turn has a positive effect on personnel performance. The mediation analysis reveals that pro-environmental behavior significantly mediates the relationships between climate change awareness and green leadership and personnel performance. These findings imply that strengthening green leadership practices and enhancing climate change awareness programs can encourage pro-environmental behavior and improve personnel performance within police organizations.